Prospects for measuring the 229Th isomer energy using a metallic magnetic microcalorimeter - Kazakov, G. A.; Schauer, V.; Schwestka, J.; Stellmer, S. P.; Sterba, J. H.; Fleischmann, Andreas; Gastaldo, Loredana; Pabinger, Andreas; Enss, Christian; Schumm, T. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2014)
The Thorium-229 isotope features a nuclear isomer state with an extremely low energy. The currently most accepted energy value, 7.8±0.5eV, was obtained from an indirect measurement using a NASA x-ray microcalorimeter with an instrumental resolution 26eV. We study, how state-of-the-art magnetic metallic microcalorimeters with an energy resolution down to a few eV can be used to measure the isomer energy. In particular, resolving the 29.18keV doublet in the γ-spectrum following the α-decay of Uranium-233, corresponding to the decay into the ground and isomer state, allows to measure the isomer transition energy without additional theoretical input parameters, and increase the energy accuracy. We study the possibility of resolving the 29.18keV line as a doublet and the dependence of the attainable precision of the energy measurement on the signal and background count rates and the instrumental resolution.
Im Titel ist die Zahl "229" hochgestellt
Available online 14 September 2013
Gesehen am 13.10.2020
This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, andreproduction in any medium, provided the original author and source are credi